Evidence that Increased Circulating 1(α),25-Dihydroxyvitamin D is the Probable Cause for Abnormal Calcium Metabolism in Sarcoidosis - Bell, Norman H. (1979)
Mean plasma 1(α),25-dihydroxyvitamin D[1(α),25(OH)(2)D] was significantly increased and serum parathyroid hormone was suppressed in three patients with sarcoidosis and hypercalcemia. Prednisone lowered the mean plasma 1(α),25(OH)(2)D to normal range and corrected the hypercalcemia. To elucidate the mechanism for the increased sensitivity to vitamin D in this disorder, the effects of orally-administered vitamin D(2) were determined in seven normal subjects, four patients with sarcoidosis and normal calcium metabolism and three patients with sarcoidosis and a history of hypercalcemia who were normocalcemic when studied. Serum and urinary calcium, serum 25-hydroxyvitamin D (25-OHD), plasma 1(α),25(OH)(2)D and, in some studies, calcium balance were measured. Vitamin D(2), 250 μg a day for 12 d, produced little, if any, change in mean plasma 1(α),25(OH)(2)D and in urinary calcium in the normals and in the patients with normal calcium metabolism. In contrast, vitamin D(2) produced increases in plasma 1(α),25(OH)(2)D from concentrations which were within the normal range (20-55 pg/ml) to abnormal values and increased urinary calcium in two patients with abnormal calcium metabolism. In an abbreviated study in the third patient, vitamin D(2), 250 μg a day for 4 d, also increased plasma 1(α),25(OH)(2)D abnormally from a normal value. There was a highly significant correlation between plasma 1(α),25(OH)(2)D and urinary calcium. Serum 25-OHD and serum calcium remained within the normal range in all subjects and patients. These findings provide evidence that the defect in calcium metabolism in sarcoidosis probably results from impaired regulation of the production and(or) degradation of 1(α),25(OH)(2)D. Prednisone may act to correct the abnormal calcium metabolism by reducing circulating 1(α),25(OH)(2)D.